Evaluation of SnO2 for sunlight photocatalytic decontamination of water. (1st July 2018) - Aslam, M.; Qamar, M. Tariq; Ali, Shahid; Rehman, Ateeq Ur; Soomro, M.T.; Ahmed, Ikram; Ismail, I.M.I.; Hameed, A.
Abstract: The broad bandgap tin (IV) oxide (SnO2 ) is the least investigated semiconductor material for photocatalytic water decontamination in sunlight exposure. A detailed study covering the synthesis, characterization and the evaluation of photocatalytic activity of SnO2, in the natural sunlight exposure, is presented. The structural characterization by XRD revealed the formation of phase pure tetragonal SnO2 with the average crystallite size of ∼41.5 nm whereas minor Sn 2+ states in the material were identified by XPS analysis. As explored by diffuse reflectance (DR) and photoluminescence (PL) spectroscopy, the material exhibited a distinct absorption edge at ∼3.4 eV. The morphological and microstructure analysis of the synthesized SnO2 was carried out by FESEM and HRTEM. The electrochemical impedance spectroscopy (EIS) and chronopotentiometry (CP) predicted the better charge transport and retention ability of the material under illumination whereas the Mott-Schottky extrapolation prophesied the n-type behavior with the flat-band potential of −0.60 V. The photocatalytic activity of SnO2 was assessed in the exposure of complete spectrum natural sunlight for the removal of 2, 4, 6-trichlorophenol. The HPLC and TOC analysis monitored the progress of degradation and mineralization whereas the released chloride ions were evaluated by ion chromatography. The effect of the transition metal ions (Fe 3+, Cu 2+, Ni 2+, and Zn 2+ ) as electron capture agents and H2 O2 as ROS generator was explored during the degradation process. The utility of the material for the simultaneous removal of chlorophenols in the mixture was also investigated. The SnO2 exhibited sustained activity in the repeated use. Based on experimental evidence congregated, the mechanism of the removal process and the efficacy of SnO2 for sunlight photocatalytic decontamination of water was established. Graphical abstract: Image 1 Highlights: Facile hydrothermal route for the synthesis of n-type SnO2. Mott-Schottky analysis prophesied the n-type behavior with the flat-band potential of −0.60 V. The flat band potential predicted the ample formation and foremost role of superoxide anions. Superoxide anion radicals are the major contributors in photocatalytic degradation process. The chloro group/s generates the active sites to facilitate the degradation process.